2019
DOI: 10.1177/1098611119862654
|View full text |Cite
|
Sign up to set email alerts
|

Police Income and Occupational Gender Inequality

Abstract: Research has found a meaningful income gap between males and females across several occupational settings, and this is also true within law enforcement. As more female workers enter the criminal justice system, it is important to revisit and update these patterns of gender inequality to account for the changing gender dynamics within this occupation. Using Current Population Survey data, we document the gender differences in pay among police over the past 28 years. Police officers experience income advantage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 81 publications
(104 reference statements)
0
17
1
1
Order By: Relevance
“…This would also lead researchers to expect a smaller gender pay gap in the public realm compared to the private labor market. Contrary to this finding, Luo et al (2019) found that police women earn consistently less than police men, and this gender income gap has remained stable over the last three decades.…”
Section: Police As a Public Sector Occupationcontrasting
confidence: 81%
See 3 more Smart Citations
“…This would also lead researchers to expect a smaller gender pay gap in the public realm compared to the private labor market. Contrary to this finding, Luo et al (2019) found that police women earn consistently less than police men, and this gender income gap has remained stable over the last three decades.…”
Section: Police As a Public Sector Occupationcontrasting
confidence: 81%
“…It is the juxtaposition between the hyper-masculine occupational settingwhere research suggests we would expect a greater degree of gender inequality (Shelley et al, 2011) and the public-sector occupationswhere we assume there will be little to no gender inequality due to the enforcement of legal precedentthat makes law enforcement the ideal place to explore within-occupational gender inequality. With increasing numbers of women entering into the police labor force (Luo et al, 2019), examining whether any gender differences in marriage's and parenthood's effects on income are present within this occupation will inform the literatures on occupational gender inequality as well as inequality within the US law enforcement.…”
Section: Police As a Public Sector Occupationmentioning
confidence: 99%
See 2 more Smart Citations
“…At the local level, the pay gap is present for women in city management roles even after accounting for human capital and organizational factors (Alkadry, Bishu, and Ali 2019). Similarly, Luo, Schleifer, and Hill (2019) report that women in policing earn 84 percent of the salary earned by their male counterparts. We know much about the gender pay gap, yet we know less about the lived workplace experiences of women in male-dominated professions.…”
mentioning
confidence: 99%